Quality of Health Care Services in Surgical-Orthopedic Wards of Jaramogi Oginga Odinga Teaching and Referral Hospital in Kisumu County, Kenya - Ogayo, Milka Awour (JOOUST, 2017)
Quality and safety of health care lead to improved client satisfaction, health outcomes; continued and sustained use of services. A public health concern has been raised on the quality of care in most hospitals, in particular surgical- orthopedic wards in sub-Saharan Africa. US reports 722,000 HAis per year. There is 1 death in 18 seconds and 7 million suffer surgical complications yearly. However, no specific study has been conducted on staffing and staff capacity, hand hygiene and aseptic technique practices, timely interventions and feedback mechanism despite the increasing clients. Therefore, this descriptive cross-sectional study using both quantitative and qualitative research methods evaluated the existing structure, in the context of quality service delivery, determined: the consistence of process as an element of quality, with the standard guidelines; the health outcome of patients with open fractures and described the experience of patients on quality of care. The study populations were 80 orthopedic patients, 34 nurses and doctors. Semi-structured questionnaire was used to collect data from both patients and staff. Staff establishment and patients' records were reviewed. Using the descriptive data analysis, the study findings showed that each nurse takes care of 30 patients or more per shift. The ratio of doctor to patient was 1: 10000. Majority of staff had not taken any other service training at the place of work, 83 .9% of nurses had diploma and above while 16.1 % were certificate holders. 22.6% of the staff strongly disagreed and 25.8% disagreed they washed hands before and after patient care even though 80.7% strongly agreed they were aware of the indications of hand hygiene. Hand sanitizer was not available inside and outside of patients' rooms. Guidelines for hand hygiene were available in the wards and clearly displayed. 41 % of fractured limbs were immobilized between 0-12 hours, 54.5% of the cases were started on prophylactic antibiotics between 0-12 hours and 86% of post¬surgery cases were discharged through surgical clinic. 87.5% of patients were aware of the existence of feedback mechanisms and mainly provided feedback through doctors and nurses. 95.8% of the patients agreed their feedback was well received and addressed promptly. 76.4% were satisfied with how the feedback was addressed. We conclude that the wards are under staffed, hand hygiene is poorly observed despite awareness of the indications. We recommend that more staff be employed by the county; hospital management to avail hand sanitizer and strengthen IPC committee; Form work improvement teams; Conduct studies to determine how health worker practice, service management and policy/rules affect the domains of quality in health care and assess access of health information by patients.